PENERAPAN PRINSIP-PRINSIP AKSESIBILITAS PADA SETTING RUANG BAGI PENYANDANG CACAT TUBUH - M. Sholahuddin S. Snv M.T. (Ars: Jurnal Seni Rupa dan Desain, 2007)
According to the WHO, the number o f physically-challenged ( - difable) people in Indonesia is 7% -20% o f the toted population and only a small proportion o f them possess adequate education and decentemployment. This condition is caused by the lack o f accessible facilities in public spaces (settingroom/interior design). In this condition, they require an institution or community which cares andencourages them to generate a positive attitude.Key Words: Setting Room/Interior Design, Accessibility, Difable.